Biorefinery of Beach Cast Seaweed in Brazil: Renewable Energy and Sustainability - Fernando Pinto Coelho; Rômulo Simões C. Menezes; Everardo Valadares de S. B. Sampaio; Márcio Gomes Barboza; Emerson Carlos Soares; Elica Amara C. Guedes-Coelho; Elvis J. de França; Agnaldo J. dos Santos; Marcelo F. de Lima; Manoel Messias da S. Costa; Natache Gonçalves de M. Ferrão; Bruno M. Soares; et al. (Phycology)
Macroalgae are a natural oceanic resource of inexhaustible abundance for the biomass energy industry with growth rates that are three to four times greater than those of terrestrial plants. The objective of this study was to evaluate the sustainability of macroalgae as biomass for biorefining through two investigations. Firstly, the deposition of macroalgae was sampled through 28 collections on seven beaches in the city of Maceió, Brazil, over a two-year period using a zigzag sampling method, covering a deposition area of 135,000 m2. From this, it was estimated that daily collection would yield 5.03 t/ha of dry biomass. Secondly, the calorific values of macroalgal biomass energy and pellet compounds were calculated. The lower calorific value (8.82 MJ/kg) found from a compound of 13 species analyzed was similar to that of the main biomass used in Brazil to obtain energy, i.e., sugarcane bagasse, which has been evaluated as 8.91 MJ/kg. Macroalgal biomass in the form of condensed energy pellets was found to have a higher calorific value of 20.18 MJ/kg, i.e., 1.2% greater than the average for terrestrial biomass pellets. Based on the results obtained, it was observed that macroalgal biomass has the possibility of becoming a new renewable feedstock with potential for bioenergy. The estimates for the deposition of biomass show possibilities for producing biofuels from marine algal raw material, which provides scope for creating another sustainable alternative for global energy issues with a reduction in environmental problems.